Kerentanan yang Dapat Terjadi di Jaringan Komputer pada Umumnya - Andre M. R. Wajong (ComTech: Computer, Mathematics and Engineering Applications, 2012)
The rapid development of computer technology allows ease of access, yet lurking threats. Security in computer networks are categorized into two, namely the physical and non physical security. Physical security is a security that is more likely to focus to all things physical. This type of security can be avoided by more careful guarding of the thieves’ threats by putting in locked places and so on. As with the non-physical security, the more important issue involved is such as data security where its physical value may be less important. Therefore, this article discussed the safety factor especially on a computer network, vulnerable points on the computer network, techniques often used on attacks and some things you can do to ward off them.